Reservoir rainfall–runoff geomorphological model. I: application and parameter analysis. Issue 4 (19th March 2012) - Goñi, M.; López, J. J.; Gimena, F. N.
Abstract This article describes and formulates a model designed to simulate runoff in wet weather events, called reservoir rainfall–runoff geomorphological model (R3GeM). In these wetlands, soil saturation is the main mechanism for the generation of surface runoff. To determine the saturated areas, the model applies a relationship based on the topographic index, between watershed storage and saturated surface. Precipitation is separated into surface runoff by saturation, subsurface runoff and losses; then, the flow of surface and subsurface runoff is performed. This hydrological model has five parameters and has been implemented in 37 events in Aixola watershed and 15 in Oiartzun watershed, both located on the Cantabrian coast of Spain. We analysed the influence of these five parameters in their behaviour, and we have proven, noting the efficiency gains, that the proposed model is valid to simulate the rainfall–runoff process. Copyright © 2012 John Wiley & Sons, Ltd.